Association of Cytochrome CYP1A1 Gene Polymorphisms and Tobacco Smoking With the Risk of Breast Cancer in Women From Iraq - Naif, Hassan M.; Al-Obaide, Mohammed A. I.; Hassani, Hayfa H.; Hamdan, Abdualghani S.; Kalaf, Zainab S. (Frontiers in Public Health, 2018)
Background CYP1A1 gene polymorphisms and tobacco smoking are among several risk factors for various types of cancers, but their influence on breast cancer remains controversial. We analyzed the possible association of CYP1A1 gene polymorphisms and tobacco smoking-related breast cancer in women from Iraq. Materials and methods In this case–control study, gene polymorphism of CYP1A1 gene (CYP1A1m1, T6235C and CYP1A1m2, A4889G) of 199 histologically verified breast cancer patients’ and 160 cancer-free control women’s specimens were performed by using PCR-based restriction fragment length polymorphism. Results Three genotype frequencies (TT, TC, and CC) of CYP1A1m1T/C appeared in 16.1, 29.6, and 54.3% of women with breast cancer, respectively, compared with 41.2, 40, and 18.8% in the control group, respectively. CYP1A1m1 CC genotype and C allele were significantly associated with increased risks for breast cancer in patients (54.3 and 69%, respectively) compared with controls (18.8 and 39%, respectively). While the three genotype frequencies (AA, AG, and GG) of CYP1A1m2A/G were detected in 20.1, 31.2, and 48.7% in patients compared with 46.3, 40.6, and 13.1% in controls, respectively. The frequency of GG genotypes and G allele was significantly higher in patients (48.7 and 64%, respectively) than in the controls (13.1 and 33%, respectively). Smoking women having either CC or GG genotypes showed a highly significant association with increased risk of breast cancer [odds ratio (OR) = 1.607, 95% confidence interval (CI) 0.91–1.64, p = 0.0001, and OR, 1.841, 95% CI, 0.88–1.67, p = 0.0001, respectively]. On the other hand, the T and A alleles of predominantly seen in healthy smoking women (83 and 85%, p = 0.0001, respectively). Conclusion These findings indicated that both C and G alleles of CYP1A1m1 and m2 were significantly associated with elevated risk of breast cancer in Iraqi women, while the T and A alleles were predominantly seen in healthy controls which may indicate their protective role. The C and G association with breast cancer incidence was more prevalent among tobacco smoking patients. These polymorphisms may be used as biomarkers of breast cancer in women from Iraq.